Perceived social support mediates between cognitive functioning and positive mental health in middle age adults - Asmat, Alia; Afzal, Saiqa; Illays, Sidra (Journal of Pakistan Psychiatric Society, 2020)
Objective: This research aims to measure the impact of cognitive functioning on positive mental health mediating role of social support among middle aged adults.Design: Correlational DesignPlace and Duration: Data was collected from February, 2018 to May, 2018 from different universities.Subject and Methods: 200 participants were selected by purposive sampling from district Faisalabad with age range of 35 to 55 years. Information was gather through Montreal Cognitive Assessment, Positive Mental Health Scale and Multidimensional Perceived Social Support.Results: Results of bivariate correlation revealed significant positive correlation between cognitive functioning and positive mental health among middle aged adults. While in mediation social support plays positive mediating role in relation between cognitive functioning and positive mental health. In gender differences results confirmed the significant difference in terms of cognitive functioning, social support and positive mental health were found.Conclusion: It can be concluded that perceived social support among middle age adults is linked with positive mental health and cognitive functioning.